Implicit Grasp Force Representation in Human Motor Cortical Recordings - Downey, John E.; Weiss, Jeffrey M.; Flesher, Sharlene N.; Thumser, Zachary C.; Marasco, Paul D.; Boninger, Michael L.; Gaunt, Robert A.; Collinger, Jennifer L. (Frontiers in Neuroscience, 2018)
In order for brain-computer interface (BCI) systems to maximize functionality, users will need to be able to accurately modulate grasp force to avoid dropping heavy objects while also being able to handle fragile items. We present a case-study consisting of two experiments designed to identify whether intracortical recordings from the motor cortex of a person with tetraplegia could predict intended grasp force. In the first task, we were able classify neural responses to attempted grasps of four objects, each of which required similar grasp kinematics but different implicit grasp force targets, with 69% accuracy. In the second task, the subject attempted to move a virtual robotic arm in space to grasp a simple virtual object. For each trial, the subject was asked to grasp the virtual object with the force appropriate for one of the four objects from the first experiment, with the goal of measuring an implicit representation of grasp force. While the subject knew the grasp force during all phases of the trial, accurate classification was only achieved during active grasping, not while the hand moved to, transported, or released the object. In both tasks, misclassifications were most often to the object with an adjacent force requirement. In addition to the implications for understanding the representation of grasp force in motor cortex, these results are a first step towards creating intelligent algorithms to help BCI users grasp and manipulate a variety of objects that will be encountered in daily life.